Stigma dan Legitimasi Agama dalam Perkawinan Disabilitas Intelektual - Dea Salma Sallom; Masdar Hilmy (PLD UIN Sunan Kalijaga, 2026)
This study examines how religious values, cultural norms, and social stigma shape marriage practices between people with intellectual disabilities and non-disabled people in Gresik. The main question is how the interaction of these three factors affects the acceptance, legitimacy, and sustainability of marriage. Using a socio-legal qualitative approach, data was collected through in-depth interviews, participatory observation, and documentation of four families as well as religious and community leaders, and analyzed using Pierre Bourdieu's framework. This study argues that marriages involving people with disabilities are carried out through a combination of religious and social capital that enables families to survive, but at the same time reinforces their dependence on external authorities. The findings show that religious and cultural values encourage acceptance, while social stigma, including stigma by association remains a major obstacle. Islamic law and religious leaders serve as sources of legitimacy as well as arenas for negotiating the concept of kafa'ah. This study emphasizes the need for a more inclusive reinterpretation of Islamic law with regard to persons with disabilities. Abstrak Penelitian ini mengkaji bagaimana nilai religius, norma budaya, dan stigma sosial membentuk praktik perkawinan antara penyandang disabilitas intelektual dan non-disabilitas di Gresik. Pertanyaan utamanya adalah bagaimana interaksi ketiga faktor tersebut memengaruhi penerimaan, legitimasi, dan keberlangsungan perkawinan. Dengan pendekatan kualitatif sosio-legal, data dihimpun melalui wawancara mendalam, observasi partisipatif, dan dokumentasi terhadap empat keluarga serta tokoh agama dan masyarakat, dianalisis menggunakan kerangka Pierre Bourdieu. Penelitian ini berargumen bahwa perkawinan disabilitas dijalankan melalui kombinasi modal religius dan sosial yang memungkinkan keluarga bertahan, namun sekaligus memperkuat ketergantungan pada otoritas eksternal. Temuannya menunjukkan bahwa nilai agama dan budaya mendorong penerimaan, sementara stigma sosial, termasuk stigma asosiatif tetap menjadi hambatan utama. Hukum Islam dan tokoh agama berfungsi sebagai sumber legitimasi sekaligus arena negosiasi konsep kafa’ah. Studi ini menegaskan perlunya reinterpretasi hukum Islam yang lebih inklusif terhadap penyandang disabilitas.